Endogenous hormonal content during grain development in hexaploid and tetraploid wheat - Gutam, Sridhar; Nath, Virendra; Srivastava, GC (Bangladesh Journal of Agricultural Research, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A pot experiment was conducted in the rabi (post rainy) seasons of 2001 and 2002 to study the genotypic differences in grain growth rate and endogenous hormonal content in the developing grains of hexaploid and tetraploid wheat. The endogenous hormonal contents of grains in both the ploidy levels had changed in sequence. At 5 days after anthesis (DAA), gibberellic acid (GA3); at 15 DAA (rapid growth phase), indole-acetic acid (IAA); at 25 DAA (dough stage), abscisic acid (ABA) were maximum. At 35 DAA, all the endogenous hormonal level decreased and among the hormones, ABA was highest followed by IAA and GA3. Hexaploids recorded higher concentrations of endogenous hormones (13.38% IAA, 17.89% GA3, and 14.7% ABA) on fresh weight basis and resulted in higher seed weight (56.99 mg/grain) and grain growth rate (0.009 g/g/day) compared to tetraploids (49.08 mg/grain; 0.008 g/g/day) on dry weight basis by better mobilization of photosynthates during grain filling. Key Words: Grain growth rate, hormones, indole-acetic acid, gibberellic acid, abscisic acid. doi:10.3329/bjar.v33i3.1608 Bangladesh J. Agril. Res. 33(3) : 493-502, September 2008